Death and the Plowman or, The Bohemian Plowman : A Disputatious and Consolatory Dialogue about Death from the Year 1400 - von Saaz, Johannes; Kirrmann, Ernest N. (Chapel Hill The University of North Carolina Press, 1958)
This dialogue about death from the year 1400 has no peer in early German Renaissance literature. Ernest Kirrmann presents an English translation of the German classic, as well as a preface by Alois Bernt giving an introduction to the context and significance of the work. The text is accompanied by five woodcuts reproduced from the earliest known printed version of the German original.
Andrew W. Mellon Foundation
National Endowment for the Humanities
English
Keywords: Fiction & related items; German Studies; Literature